An integrative genomics approach identifies KDM4 as a modulator of trained immunity. Issue 3 (10th December 2021) - Moorlag, Simone J.C.F.M.; Matzaraki, Vasiliki; van Puffelen, Jelmer H.; van der Heijden, Charlotte; Keating, Sam; Groh, Laszlo; Röring, Rutger Jan; Bakker, Olivier B.; Mourits, Vera P.; Koeken, Valerie A.C.M.; de Bree, L. Charlotte J.; Smeekens, Sanne P.; et al.
Abstract: Innate immune cells are able to build memory characteristics via a process termed "trained immunity." Host factors that influence the magnitude of the individual trained immunity response remain largely unknown. Using an integrative genomics approach, our study aimed to prioritize and understand the role of specific genes in trained immunity responses. In vitro‐induced trained immunity responses were assessed in two independent population‐based cohorts of healthy individuals, the 300 Bacillus Calmette‐Guérin (300BCG; n = 267) and 200 Functional Genomics (200FG; n = 110) cohorts from the Human Functional Genomics Project. Genetic loci that influence cytokine responses upon trained immunity were identified by conducting a meta‐analysis of QTLs identified in the 300BCG and 200FG cohorts. From the identified QTL loci, we functionally validated the role of PI3K‐Akt signaling pathway and two genes that belong to the family of Siglec receptors (Siglec‐5 and Siglec‐14). Furthermore, we identified the H3K9 histone demethylases of the KDM4 family as major regulators of trained immunity responses. These data pinpoint an important role of metabolic and epigenetic processes in the regulation of trained immunity responses, and these findings may open new avenues for vaccine design and therapeutic interventions. Abstract : Using an immunogenomics approach, we identify genetic factors explaining interindividual variation in in vitro‐induced trained immunity responses. We highlight novel factors controlling trained immunity, including the KDM4 family of histone demethylases. These findings shed light on mechanisms underlying trained immunity and offer novel avenues for the design of therapeutics.